A Framework for Social Innovation: Unveiling the 5Ps of Policy Entrepreneurship - Jain, Vipin (Journal of Advanced Research in HR and Organizational Management, 2023)
Policy, as a set of guidelines aimed at steering change within a society, often undergoes transformation through the efforts of policy entrepreneurs. These individuals actively engage with various entities to implement and influence policy changes. This article explores the emerging field of policy entrepreneurship, presenting a qualitative analysis of Indian policy entrepreneurs. The study introduces a conceptual model, the 5Ps of policy entrepreneurship - Passion, Purpose, Publicity, Participation, and Presentation - identifying them as crucial social innovations in achieving transformative policy initiatives. This research sheds light on how policy entrepreneurs strategically leverage these factors to bring about desired policy changes.